Asymmetric price volatility transmission between food and energy markets: The case of Spain. (14th May 2015) - Abdelradi, Fadi; Serra, Teresa
Abstract The proportion of agricultural production that is being transformed into biofuels has been growing worldwide over the last decade. This has spurred the food versus fuel debate. This article aims at shedding light on this issue by studying price volatility relationships between food and biofuel prices in Spain. We use an asymmetric MGARCH model to evaluate volatility spillovers between the Spanish biodiesel blend and refined sunflower oil prices. Empirical results confirm that there are bidirectional and asymmetric volatility spillovers between these two prices.